Bahaya minuman khamar dalam pandangan islam dan kesehatan - Rochiyana, Luluk (Maliki Interdisciplinary Journal, 2023)
Alcoholic beverages, known as khamr, have long been a complex issue in both religious and health perspectives. This article delves into the dangers of alcoholic beverages from the Islamic viewpoint and human health aspect. In the context of Islamic beliefs, khamr is considered a substance that impairs rationality, disrupts morality, and is explicitly prohibited in religious teachings. Additionally, the article analyzes the social and cultural implications of alcohol consumption within an Islam-based society. In terms of health, the consumption of alcoholic beverages has been proven to cause various serious health problems, including liver disorders, mental disturbances, and a higher risk of accidents. Through an interdisciplinary approach, this article illustrates how Islamic views and modern health science can complement each other in discussing the adverse effects of alcoholic beverages on individuals and societies.